Metagenome Sequencing Reveals the Midgut Microbiota Makeup of Culex pipiens quinquefasciatus and Its Possible Relationship With Insecticide Resistance - Wang, Yi-ting; Shen, Rui-xin; Xing, Dan; Zhao, Chen-pei; Gao, He-ting; Wu, Jia-hong; Zhang, Ning; Zhang, Heng-duan; Chen, Yan; Zhao, Tong-yan; Li, Chun-xiao (Frontiers in Microbiology, 2021)
Midgut microbiota can participate in the detoxification and metabolism processes in insects, but there are few reports on the relationship between midgut microbiota and insecticide resistance in mosquitoes. In this study, we performed metagenomic sequencing on a susceptible strain (SS), a field-collected Hainan strain (HN), and a deltamethrin-resistant strain (RR) of Culex pipiens quinquefasciatus to understand the diversity and functions of their midgut microbiota. The results revealed differences in midgut microbiota among the three strains of Cx. pipiens quinquefasciatus. At the phylum level, Proteobacteria was the most prominent, accounting for nearly 70% of their midgut microbes. At the genus level, Aeromonas made up the highest proportion. In addition, Aeromonas, Morganella, Elizabethkingia, Enterobacter, Cedecea, and Thorsellia showed significant differences between strains. At the species level, Bacillus cereus, Enterobacter cloacae complex sp. 4DZ3-17B2, Streptomyces sp. CNQ329, and some species of Pseudomonas and Wolbachia were more abundant in the two resistant strains. Principal component analysis (PCA) showed that the SS strain had significantly different metagenomic functions than the two deltamethrin-resistant strains (HN and RR strain). The HN and RR strains differed from the SS strain in more than 10 Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways. The analysis of species abundance and functional diversity can provide directions for future studies.